19th CENTURY OTTOMAN MACEDONIA IN WESTERN HISTORY BOOKS (Annual of the Faculty of Philosophy in Skopje, 2011)
In this article I will attempt to present how some western historians who deal with the Balkan past perceived Macedonia as it was during the last century of the Ottoman rule. The focus of this paper will be on how 19th century Ottoman Macedonia is represented in the general history books on the Balkans written in the west. In writing this paper I made use of those works that have been, up to now, most widely used by the historians, as well as the ordinary people, who like and appreciate historical literature. The main accent in this article is stressed on several issues namely - the territory, the population, political history, economical and social life. In this instance I made use of books dealing with the history of the Balkans published after WWII, i.e., after the creation of the modern Macedonian state. One should bear in mind that Macedonia was not authors primary focus of research and writing, and for this reason the mistakes that appear, and which we all make when we write, are understandable, but not acceptable. We must note that, despite all the criticism that might be directed at them, they have made an honest attempt, to their best of their knowledge and ability, to portray the situation in Ottoman Macedonia in the 19th century, paying attention not to favor any one side.